USING STORY FACE STRATEGY IN TEACHING READING NARRATIVE TEXT AT JUNIOR HIGH SCHOOL - Maitri Lusiana; Yetti Zainil (Journal of English Language Teaching, 2018)
This paper discusses how to use Story Face Strategy in teaching reading narrative text at Junior High School. Based on the writers‟ experience in teaching English, many students find the difficulties in reading narrative text. Considering this  problem,  the  teacher  needs  to  apply  a  strategy in  teaching  and  learning process to help the students understand the text. Story Face Strategy is a graphic organizer that aids reading comprehension of narrative text. Story face is constructed by making the eyes: two circles representing the setting and main characters,   eyelashes:  specific   descriptors  and   secondary  characters,   nose: problem, and mouth: comprises a series of circles representing the main events that  lead  to  the  solution.  It  functions like  a  story map,  allowing  students  to visualize the important component of narrative text, including setting, main characters,  problems,  events,  and  a  resolution.  By  applying  the  Story  Face Strategy in reading narrative text, the teacher can reach the goal of teaching narrative text to junior high school students. Key words: reading, narrative text, story face strategy